Carbon nuclear magnetic resonance studies of conformational equilibria - Barna, J (1981)
One bond coupling constants were measured as a function of temperature for bonds between carbon and carbon (lJCC) and, less commonly, hydrogen (lJCH) or fluorine (lJCF). Precisions of ±0.01 Hz were achieved using double isotopic substitution (for lJCC) and least squares curve fitting. Temperatures were measured to ±0.5 K using carbon chemical shift thermometers. Molecules having no conformational equilibria showed substituent, temperature and solvent effects on the couplings, throwing doubt on some conformational uses of higher order couplings. Comparison of lJCC values and their temperature dependences (ΔJ/ΔT) for some amines and appropriate models allowed determination of conformational free energies (ΔG°) . ΔG° was estimated for some ethylamines (trans and gauche conformers) and for piperidine (axial and equatorial N-H) . The method depends on the differences in lJCC for a bond in an ethyl group (ethylamines) or ring (piperidines) according to whether it is cis, gauche, or trans to a nitrogen lone pair. Conformational information was generally obtained from comparison of absolute lJCC , values, not from ΔJ/ΔT. A hindered internal rotation of the ethyl in r-2,c-4,c-6-trimethyl-N-ethylpiperidine was discovered; lJCC was observed for separate conformers at low temperature and ΔG° was estimated at room temperature. The result was compared with ΔG°s obtained using other carbon n.m.r. methods, i.e., measurement of line broadening, integrated resonances at low temperature and averaged chemical shifts. Axial /equatorial equilibr were studied by known n.m.r. methods for N-ethyl- and analogous N-methyl-piperidines . lJCC is dependent on conformation in [(l3C2)ethyl] benzene and its mesityl analogue; mathematical treatment should provide an estimate of the barrier to rotation in ethylbenzene. lJCC is dependent on conformation in ketones (e.g. diethylketone) and on the configuration (syn/anti) of their derivatives. Hyperconjugation with unsaturated centres explains the conformational dependences of lJCC , analogous to those known for lJCH.